Analysis of Rehabilitation Services for Clients with Drug Addiction - Anndiny Anastasya Handayani; Siti Jaroah (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Despite numerous efforts at rehabilitation, drug abuse remains a significant issue in Indonesia. The purpose of this study is to describe and analyze the rehabilitation services offered by Badan Narkotika Nasional (BNN) Surabaya. Through in-depth interviews, observations, and documentation studies of ten informants, who were clients and professionals, the study employed qualitative methods with a case study design. The findings indicated that the majority of BNN Surabaya’s clients are methamphetamine users and that the facility only offers outpatient rehabilitation services. The rehabilitation procedure is carried out in accordance with the relevant technical guidelines and is free of charge. However, there are a number of barriers to its implementation, including sporadic client attendance, relapse risk, distance limitations and a shortage of counselors. The results of this study are related to Bandura’s social cognitive theory, which highlights the significance of social influence, self–efficacy, and environmental factors in effective rehabilitation. Rehabilitation programs must focus on a thorough biopsychosocial approach in order to promote the best possible outcome for clients recovery.